2017
DOI: 10.1080/17453674.2017.1319179
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spinal cord compression as the first sign of malignancy

Abstract: Background and purposeMetastatic spinal cord compression (MSCC) as the initial manifestation of malignancy (IMM) limits the time for diagnostic workup; most often, treatment is required before the final primary tumor diagnosis. We evaluated neurological outcome, complications, survival, and the manner of diagnosing the primary tumor in patients who were operated for MSCC as the IMM.Patients and methodsRecords of 69 consecutive patients (51 men) who underwent surgery for MSCC as the IMM were reviewed. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…Whilst spinal cord compression may be non-malignant in origin and present in people with or without cancer, MSCC can be the first presentation of an undiagnosed primary cancer which has progressed, or may reflect secondary disease (Wanman et al, 2017). Any cancer has the potential to metastasise to the spine, but MSCC most commonly presents in breast, lung and prostate cancer, lymphoma and myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst spinal cord compression may be non-malignant in origin and present in people with or without cancer, MSCC can be the first presentation of an undiagnosed primary cancer which has progressed, or may reflect secondary disease (Wanman et al, 2017). Any cancer has the potential to metastasise to the spine, but MSCC most commonly presents in breast, lung and prostate cancer, lymphoma and myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [ 14 ] in 2012 reported a prospective cohort study of 448 patients with spinal metastases and found that the median duration of survival in the UPT group was 11.4 mo, which was much better than that in the lung cancer group (3.0 mo), but worse than that in the breast cancer group (21.5 mo). In contrast, two independent studies in 2017 both mentioned that patients with UPTs had the shortest survival (3.5 mo and 4.6 mo, respectively) among all patients with metastatic spinal disease[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the study published in 2014 by Quraishi et al [ 20 ], 10 of the 17 unidentified metastatic tumors were confirmed to be adenocarcinoma postoperatively, with 6 derived from pulmonary cancer and 4 from gastrointestinal cancer. However, most of the time, even though intraoperative bone biopsy confirmed the pathological features of metastatic lesions, up to the endpoint of the study their original sites might still not have been ascertained[ 15 ]. Similarly, in our case, although the thoracic vertebral lesion had undergone both preoperative and postoperative pathological analyses, due to the rapid deterioration of the disease and the absence of either pulmonary mass biopsy or autopsy, the relationship between the metastatic tumor and the pulmonary lesion remains dubious.…”
Section: Discussionmentioning
confidence: 99%
“…MSCC predominantly affects the thoracic vertebrae (65) followed by the lumbosacral (25) and cervical region (10) [2]. 20-35 of patients have multiple sites of MSCC on imaging [1]…”
Section: Anatomical Distribution Of Msccmentioning
confidence: 99%